Sensitivity of L132 Cells to Some “New” Respiratory Viruses - BRADBURNE, A. F. (Nature, 1969)
THERE are several reports of the isolation from cases of human upper respiratory infections of viruses with a structure known previously only in the viruses causing avian infectious bronchitis(1) and mouse hepatitis(2). The first isolate, named B814, was propagated in organ cultures of human embryo respiratory epithelium(3), and most of the other isolates have been made in organ culture(4). Some viruses of humans, of the type 229E, multiply in tissue cultures of human embryo kidney fibroblasts where they cause a slight cytopathic effect, and in human embryo lung fibroblasts where they cause a definite progressive cytopathic effect(5). Those viruses only cultivated in organ culture were detected either by electron, microscopy, or by inoculation into human volunteers, or by stopping the ciliary activity of the organ culture epithelium. It has been proposed that the group of virsues with this morphology should be called “coronaviruses”(6).